Brand ladder as a positioning strategy in rehabilitation, physiotherapy and kinesiology centers of the city of Riobamba - Diaz Campaña, Josselyn (mktDESCUBRE; Vol 1 No Especial (2021): Special Edition 4th International Scientific Congress of Administrative and Financial Sciences FADE 2020DO - 10.36779/mktdescubre.v1iEspecial.567, 2021)
The success of applying Brand Ladder in the rehabilitation, physiotherapy and kinesiology centers of the city of Riobamba is that thanks to the establishment of attributes benefits, functional, emotional, transformational and social, the company will be able to gain presence or position among the competition and its customers. The purpose of the research is to inform physiotherapy rehabilitation centers about the brand ladder, which will contribute to improving their positioning, through the identification of their benefits. To do this, a survey was applied to a group of marketing experts in order to question the Brand Ladder strategy and find out if it is acceptable to run it in rehabilitation and physical therapy centers. A qualitative and quantitative approach was used, as well as a descriptive and explanatory level of research; the research design is established to be non-experimental. According to the results of the survey, it is established that 84.8% consider that the Brand Ladder strategy will help rehabilitation, physiotherapy and kinesiology centers to have a greater presence and position in the city of Riobamba. This article is of a scientific review type.